Produção de bioherbicida por processos fermentativos a partir do fungo Phoma sp. - Klaic, Rodrigo (2014)
Weeds are one of the major problems in the agricultural products cultivation and the main strategy of control is the use of chemical herbicides. Although is efficient, the herbicides bring direct and indirect consequences that overcome its benefits and this opened the way for bioherbicides. A significant barrier in the bioherbicide production is the development of an economically viable fermentation process. This way the aim of this work was to assess the production of a bioherbicide from the Phoma sp. fungus by submerged fermentation and solid-state fermentation, optimizing the fermentation medium in both cases and evaluating the herbicidal activity from the fermentation extracts in the control of the target plants. The culture medium was optimized and the cell growing was monitoring as response in the submerged fermentation. The optimum composition for the synthetic medium was glucose and peptone at 20 gL-1, yeast extract 7.5 gL-1 and an initial pH of 6.0. For the industrial medium, the ideal composition was 20 gL-1 of sucrose, 8 % CSL and initial pH of 6.0. Under these conditions, the maximum biomass obtained was 22 and 33 gL-1, for the synthetic and industrial medium, respectively. Therefore it was possible to obtain a 50 % higher biomass production in the industrial medium, reducing the cost of this fermentation medium. In the solid fermentation the composition of the culture medium was evaluated for obtaining the maximum herbicide action on target plants (cucumber). Bioassays were realized and the plant height, fresh weight, dry weight and phytotocixity mainly were the responses evaluated. The results obtained in the bioassays demonstrate that the bioherbicide presented activity towards the target plant and the intensity of the effect was influenced by the formulation of the fermentation medium. The optimized condition for bioherbicide production was moisture at 70 %, soybean bran of 30 wt% and CSL of 20 wt%, being possible to obtain a moderate injury, usually with recovery. The bioherbicide produced showed a mode of action based on the inhibition of carotenoids biosynthesis.